Analisis Pengaruh Konfigurasi dan Dimensi Dinding Geser (Shear Wall) terhadap Persyaratan Simpangan dan Torsi Struktur Bangunan Gedung - Khoirul Anwar; Sumirin Sumirin; Abdul Rochim (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Indonesia is in an earthquake-prone region, therefore, designing building constructions that can withstand seismic loads is crucial in civil engineering. Reinforced concrete shear walls are one of the vertical structural fundamentals that are effectively used in multi-story buildings to withstand lateral forces due to earthquake and wind loads. Structures that use shear walls can increase stiffness and reduce horizontal deviations (deflections) of buildings, which contribute to the stability and safety of structures based on the SNI 1726:2019 standard. This study aims to analyze the effect of shear wall configurations on deviation and torsion requirements in multi-story building planning. The study object is a 6-story reinforced concrete building model in a specific earthquake zone. The design and modeling were performed using structural analysis software, taking into account columns, beams, slabs, and shear walls. The analysis results show that optimal placement of shear walls at the building edges significantly reduces horizontal drift, torsion, and shear forces, and improves the structural performance level compared to structures without shear walls or those with less effective placement. Structures with shear walls have optimal stiffness in absorbing lateral forces, making them more resistant to damage from the planned earthquake.